Magnitude of maximum shoulder and hip roll angles in back crawl at different swimming speeds - Gonjo, T.; McCabe, C.; Coleman, S.; Sanders, R. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to identify the characteristics of maximum shoulder and hip roll angles in back crawl at different swimming speeds. Ten male elite swimmers performed back crawl at four different swimming speeds. The swimming trials were filmed by a total of six digital video cameras and three-dimensional coordinates of swimmer's anatomical landmarks were calculated using the three-dimensional direct linear transform. The data were input to a MATLAB programme to calculate linear and angular kinematics. Among the four speed trials, maximum shoulder and hip roll angles were unchanged, and maximum shoulder roll angle was significantly larger than maximum hip roll angle in all trials. In conclusion, the swimming speed does not affect swimmer's shoulder and hip roll angles in back crawl swimming.